CCAFS: A proposed new agenda for research and development - Campbell, Bruce M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Presentation by CGIAR Climate Program Director Bruce Campbell. Mr. Campbell talks about a new agenda for research and development. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya.